Aspectos ecofisiológicos do Pirarucu (Arapaima gigas) na área de Proteção Ambiental Nhamundá, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The present thesis describes the main ecophysiological aspects of pirarucu (Arapaima gigas) adults and fingerlings coming from aquatic environments of the Nhamundá Environmental Protection Area (APA). The APA Nhamundá is a confluence between the Nhamundá (black water) and the Amazonas (white water) rivers, which allow to form several intermediates resulting from the water supply of one of the rivers. The pirarucu is a rustic animal and, from the physiological point of view, is phenotypically plastic capable of tolerating different types of environments. In this sense, adult specimens of A. gigas captured in five lakes within the APA Nhamundá were analyzed. For this animals, reference values for hematology, plasma biochemistry (hemoglobin, erythrocytes, hematocrit, hematimetric indexes, plasma ions and nitrogen metabolites), metabolic enzymes (lactate dehydrogenase, LDH and malate dehydrogenase, MDH) and body indexes (condition relative and condition factor). It was observed that the parameters of the blood physiology, as well as enzymatic, are closely associated with the physical and chemical characteristics of each environment where the fish was collected. To test the hypothesis that the physiological and metabolic variables are influenced by the chemical and physical characteristics of the environment, juveniles weighing 20-75 g (16-23 cm total length) were experimentally maintained for 7 and 14 days in the black water of the Nhamundá River, white water of the Amazon River and in nursery (excavated tank). In these specimens the body, hematological, biochemical of the plasma indexes and the enzymatic activity of LDH and MDH in different tissues were analyzed. As observed in adult animals, hematological parameters and metabolic enzymes varied according to the physical and chemical characteristics of the water where the fish remained submitted. . Therefore, both juveniles and pirarucu adults showed high physiological and metabolic plasticity in relation to different types of water (with profound variations in pH, conductivity, salt concentration, hardness, alkalinity, transparency and oxygen concentration). These results provide physiological explanations about the rustic and adaptive characteristics of pirarucu in different environments in the Amazon.
Keywords: Ambientes Amazônicos; Arapaima; Tipos de Água; Pirarucu (Arapaima gigas); CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA